2020
DOI: 10.1111/clr.13637
|View full text |Cite
|
Sign up to set email alerts
|

Do implant‐retained mandibular overdentures maintain radiographic, functional, and patient‐centered outcomes after 3 years of loading?

Abstract: Objectives: Analyzing whether radiographic, functional, and oral health-related quality of life (OHRQoL) outcomes are maintained over 3 years of implant-retained mandibular overdenture (IMO) function and investigating the bite force associations in the 3rd year of function. Material and methods: A longitudinal clinical study in which 24 IMO users were evaluated during a 3-year follow-up period. Patients' posterior area index, masticatory function, OHRQoL and bite force were assessed. The masticatory function p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Mukilvannan et al (2021) reported higher OHIP scores and satisfaction of edentulous patients treated with two‐implant mandibular overdentures and this positive effect did not change 8–10 years after treatment. In contrast, Possebon et al (2020) showed that patient satisfaction with their dentures began to decrease 3 years after the dentures were fitted, possibly because of declining mucosal support in the posterior region. Another study showed that OHIP scores and implant stability improved from 1 year after the start of loading until 4 years after the start of loading, but then worsened in the fifth year of follow‐up.…”
Section: Discussionmentioning
confidence: 94%
“…Mukilvannan et al (2021) reported higher OHIP scores and satisfaction of edentulous patients treated with two‐implant mandibular overdentures and this positive effect did not change 8–10 years after treatment. In contrast, Possebon et al (2020) showed that patient satisfaction with their dentures began to decrease 3 years after the dentures were fitted, possibly because of declining mucosal support in the posterior region. Another study showed that OHIP scores and implant stability improved from 1 year after the start of loading until 4 years after the start of loading, but then worsened in the fifth year of follow‐up.…”
Section: Discussionmentioning
confidence: 94%
“…While not yet constituting the standard of care [1] in all countries, implant-retained removable prostheses have been shown to have a positive effect on functional and patientcentered outcomes [2][3][4]. In this context, a large body of literature comparing various implant and attachment configurations [5] does exist, at least partially reporting contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…3 This system is intended for use in mandibles with limited bone availability. Several aspects of Equator attachments used as MO retainers have been studied, such as their relationship with quality of life, masticatory function, 4,5 clinical periimplant, and biological aspects, 6,7 and performance according to loading protocols. 8 However, little is currently known about the profile of complications and prosthetic events that may be related to the Facility-Equator system, and these data are essential for patients and clinicians as they permit to develop a more holistic prognostic measure that helps in the selection of implant systems.…”
Section: Introductionmentioning
confidence: 99%